3D analytical modeling of the ultra-high-speed permanent magnet electrodynamic levitation system and analysis of electromagnetic force characteristics - HU Yongpan; CHEN Baojun; LONG Zhiqiang (机车电传动)
The permanent magnet electrodynamic levitation system has been proven significantly valued for applications in ultra-high-speed tube magnetic levitation transport, due to its self-stabilizing performance at high speeds and easy installation and maintenance. This paper focused on the ultra-high-speed permanent magnet electrodynamic levitation system and presented a method for constructing boundary conditions for transverse end sections, by modeling the "Halbach permanent magnet array—conductor plate" structure. Additionally, a method to solve the electromagnetic force was proposed. By analyzing the change rules of electromagnetic force with electromagnetic parameters and structural parameters, this paper revealed the characteristics of electromagnetic force. The principle of the electromagnetic force model was validated through a comparison between the finite element simulation results and findings from a verification experiment carried out on a rotary experimental platform.